Information Systems Strategic Planning at one of the Vocational High Schools in Cimahi - Imannudin Akbar Iman; Venia Restreva Danestiara; Syahira Putri Himmaniah (Jurnal Computech & Bisnis (e-journal), 2024)
A strategic plan is an organization's detailed and extensive strategy to effectively manage its resources and achieve its goals within a specified period. Effective implementation of an information system necessitates strategic planning inside an organization to capitalize on the advantages of the information system implementation fully. This also applies to a Vocational High School in Cimahi. The school encounters many obstacles, including managing school data and performance assessments and requiring a unified system across departments to facilitate the school's operational procedures. Strategic planning establishes specific objectives, such as integrating information systems in academic and non-academic operations, overseeing school data management, enhancing infrastructure management efficiency, and boosting competitiveness by developing a web-based school support system for information and promotional purposes. Aligning the information system's strategies with the school's business strategies will aid in accomplishing these objectives. Developing information system strategies necessitates alignment with the organization's existing business strategies. This research examines the strategic information system planning process, specifically employing the Ward-Peppard technique. This approach facilitates a more comprehensive comprehension of the firm before developing a strategic plan. It involves doing a SWOT analysis, Value Chain analysis, Porter's Five Forces analysis, and McFarlan's strategic grid analysis as recommendations for the proposed information system strategies.